Edukasi Bahaya Game Online Pada Remaja - Efni, Nel; Fatmawati, Tina Yuli (Prosiding Seminar Kesehatan Nasional, 2023)
Adolescence is a transition period from childhood to adulthood. During this period there are many rapid changes that need attention from parents. The use of gadgets at school is considered to have disrupted children's health and social relationships. When a child is addicted to playing online games, it will make the child feel anxious if separated from gadgets. The aim of this community service is for students to understand the dangers of online games. The methods used in community service are lectures, discussions, questions and answers and providing educational media, namely leaflets. A series of service activities were carried out for 45 students of SMA N 4 Jambi City. The results of community service obtained an average student knowledge before education of 4.2 and after education of 8.8. This means that there was an increase in students' knowledge before and after education with an average of 4.6. Online games can affect children's brain development. Therefore, the role of parents is very important in accompanying children. Parents must know the limits of when children are allowed to play online games and how long children can play online games..Â